Masa Depan dan Problem Metodologi Studi Islam - Minhaji, Akh. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
The debate over Islamic law is more dominated by practical issues (fiqh) and very rarely touches on theoretical or methodological issues (usul al-fiqh), no exception concerning gender issues. This paper discusses the methodology of Islamic jurisprudence to use as a basis for examining Islamic legal issues. The discussion presents the nuance of a shift in values which in turn demands evaluation of ushul al-fiqh thought. Basically, it is realized that there has been a shift in values that affect the ummah in looking at the problems faced. This influence occurs not only on the practical level but also at the paradigm used in viewing reality. The change in values requires an evaluation of the heritage of the religious study model. Without evaluation efforts, it can be ascertained that ushul al-fiqh increasingly has no place in the debate over the methodology of religious studies. It is the symptom existing today which is also a challenge for those pursuing Islamic law studies. What is stated in this paper is the first step to uncover the stagnation and vacuum of thinking in the field of ushul al-fiqh.